2011
DOI: 10.1063/1.3551758
|View full text |Cite
|
Sign up to set email alerts
|

Wave propagation and noncollisional heating in neutral loop and helicon discharges

Abstract: Heating mechanisms in two types of magnetized low pressure rf ͑13.56 MHz͒ discharges are investigated: a helicon discharge and a neutral loop discharge. Radial B-dot probe measurements demonstrate that the neutral loop discharge is sustained by helicon waves as well. Axial B-dot probe measurements reveal standing wave and beat patterns depending on the dc magnetic field strength and plasma density. In modes showing a strong wave damping, the plasma refractive index attains values around 100, leading to electro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 48 publications
0
11
0
Order By: Relevance
“…19 The theoretical predictions of the anomalous skin effect have been well confirmed experimentally. [20][21][22][23] In recent years, various antenna coil geometries have been reported, e.g., solenoid, planar, or dome shapes. [24][25][26] Further, small single loop elements oriented perpendicular to the wall have been proposed for being arranged in large arrays in order to overcome the spatial size limits set by single coils.…”
Section: Introductionmentioning
confidence: 99%
“…19 The theoretical predictions of the anomalous skin effect have been well confirmed experimentally. [20][21][22][23] In recent years, various antenna coil geometries have been reported, e.g., solenoid, planar, or dome shapes. [24][25][26] Further, small single loop elements oriented perpendicular to the wall have been proposed for being arranged in large arrays in order to overcome the spatial size limits set by single coils.…”
Section: Introductionmentioning
confidence: 99%
“…To obtain in situ information about the amplitude and the phase of the induced electric field as well as information about the strength of the capacitive coupling compared to the inductive coupling into the plasma an optical diagnostic called radio frequency modulation spectroscopy (short: RFMOS) is used [13][14][15] . For this diagnostic the temporal modulation of the emission from a chosen line (from now on called modulation) is measured using an ICCD camera.…”
Section: A Rf Modulation Spectroscopy (Rfmos)mentioning
confidence: 99%
“…To obtain a relation between the intensity modulation ηnω and the electric field the following approach is applied. The rate equation for the excited state is combined with the assumption of a time independent, isotropic near Maxwellian distribution of the electrons that is displaced by a small, time dependent oscillation velocity [13][14][15] . From this, the measured modulation η(1,2)ω can be expressed as follows:…”
Section: A Rf Modulation Spectroscopy (Rfmos)mentioning
confidence: 99%
“…This process is called partial electron cyclotron resonance (PECR). Finally, a collisionless wave damping mechanism in the complex magnetic field of the NL setup has been proposed [9]. In that setup, a helicon wave field is observed that is modified by the presence of a magnetic NL configuration.…”
Section: Introductionmentioning
confidence: 99%
“…Due to the well controlled density profile, these discharges can be used for precise plasma etching via the direct control of the NL radius [4]. Several concurrent plasma production mechanisms have been proposed to account for the increased plasma density near the NL [1,[5][6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%